2016
DOI: 10.3109/01902148.2016.1157712
|View full text |Cite
|
Sign up to set email alerts
|

Prior hypoxia prevents downregulation of ACE-2 by hyperoxia in fetal human lung fibroblasts

Abstract: Purpose/Aim of Study The renin angiotensin system is involved in experimentally induced lung fibrosis. Angiotensin (ANG)-II is profibrotic. Angiotensin converting enzyme-2 (ACE-2) cleaves ANG-II and is thus protective. ACE-2 has recently been reported to be significantly decreased under hyperoxic conditions. Hyperoxia is linked to Bronchopulmonary Dysplasia and lung fibrosis. Fetal lung cells normally do not undergo fibrotic changes with physiologic hypoxemia. We hypothesized that hypoxia prior to hyperoxic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Our study is limited by small sample size, and the fact that it used adult human lung AECs. However, our laboratory has demonstrated the presence of ACE-2 in neonatal mouse lung as well as in fetal lung fibroblasts [36,37]. Therefore, it is plausible that a similar effect of meconium on fetal and neonatal lungs would be observed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our study is limited by small sample size, and the fact that it used adult human lung AECs. However, our laboratory has demonstrated the presence of ACE-2 in neonatal mouse lung as well as in fetal lung fibroblasts [36,37]. Therefore, it is plausible that a similar effect of meconium on fetal and neonatal lungs would be observed.…”
Section: Discussionmentioning
confidence: 91%
“…Also, we have not examined the direct effect of downregulation of ACE-2 and meconium-induced apoptosis in this study. Nevertheless, our laboratory has previously shown that ACE-2 downregulation leads to apoptosis of human A549 cells, MLE12 cells and fetal fibroblast IMR 90 cells in response to various noxious stimuli, e.g., bleomycin [18], hyperoxia [36] and hypoxia [37]. Therefore, it is safe to assume that meconium-induced human A549 cells apoptosis is due to downregulation of ACE-2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to liver disease, ACE-2 has been shown to play an established protective role in lung disease through effects mediated by Mas oncogene, the ACE-2 peptide product ANG1-7 receptor. 54,73─75 Previous studies from our lab and other groups suggest that ACE-2 is down-regulated in fibrotic conditions of the adult and neonatal human lung 54,73,74 via Mas receptor mechanisms. 70 Data from our lab was first to discover the significant decrease of ACE-2 in the human IPF lung and identify the protective effects of ACE-2 in the IPF disease.…”
Section: Ace-2 and Pulmonary Fibrosismentioning
confidence: 93%
“…27 Supplemental oxygen, which is frequently used in the treatment of pulmonary insufficiency in premature infants, has been implicated in the development of BPD. 73,74 In adult animal models of acute lung injury, 79,80 ACE-2 was shown to inhibit lung edema formation and inflammation as well as fibrogenesis. However, little is known about the role of ACE-2 in neonatal models of BPD.…”
Section: Ace-2 and Bronchopulmonary Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation